Gene expression profiling in aggressive digital papillary adenocarcinoma sheds light on the architecture of a rare sweat gland carcinoma. (1st May 2019) - Surowy, H.M.; Giesen, A.K.; Otte, J.; Büttner, R.; Falkenstein, D.; Friedl, H.; Meier, F.; Petzsch, P.; Wachtmeister, T.; Westphal, D.; Wieczorek, D.; Wruck, W.; et al.
Summary: Background: Sweat gland carcinomas are rare cutaneous adnexal malignancies. Aggressive digital papillary adenocarcinoma (ADPA) represents a very rare subentity, thought to arise almost exclusively from the sweat glands of the fingers and toes. The aetiology of sweat gland carcinomas and ADPA is largely unknown. ADPAs are most likely driven by somatic mutations. However, somatic mutation patterns are largely unexplored, creating barriers to the development of effective therapeutic approaches to the treatment of ADPA. Objectives: To investigate the transcriptome profile of ADPA using a sample of eight formalin‐fixed, paraffin‐embedded tissue samples of ADPA and healthy control tissue. Methods: Transcriptome profiling was performed using the Affymetrix PrimeView Human Gene Expression Microarray and findings were validated via reverse transcription of RNA and real‐time quantitative polymerase chain reaction. Results: Transcriptome analyses showed increased tumour expression of 2266 genes, with significant involvement of cell cycle, ribosomal and crucial cancer pathways. Our results point to tumour overexpression of FGFR2 ( P = 0·001). Conclusions: The results indicate the involvement of crucial oncogenic driver pathways, highlighting cell cycle and ribosomal pathways in the aetiology of ADPA. Suggested tumour overexpression of FGFR2 raises the hope that targeting the fibroblast growth factor (FGF)/FGF receptor axis might be a promising treatment for ADPA and probably for the overall group of sweat gland carcinomas.